2018
DOI: 10.1039/c8ra08491b
|View full text |Cite
|
Sign up to set email alerts
|

A NIR light-triggered pyroelectric-dominated generator based on a liquid crystal elastomer composite actuator for photoelectric conversion and self-powered sensing

Abstract: Transducing light into electricity in photoactive materials and composites is especially attractive for light sensing and light energy harvesting. Here, we present a near-infrared (NIR) light-triggered pyroelectricbased generator by integrating a photoresponsive composite actuator composed of a liquid crystal elastomer (LCE) and graphene-doped poly(dimethylsiloxane) (PDMS) into a polyvinylidene fluoride (PVDF) film, which can effectively convert photothermal and mechanical energy into electricity. Notably, a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The twisting deformation of a soft CPs/LCE actuator could generate incompatible strain to propel the actuator roll forward. Compared with other millimeter-scale NIR light-induced soft actuators reported in the literature, 6,[47][48][49][50] the CPs/LCE actuators proposed here exhibit a faster response time (within 1 s), more significant deformation potential (1801 bending angle) and higher locomotion speed (0.47 mm s À1 ).…”
Section: Introductionmentioning
confidence: 82%
“…The twisting deformation of a soft CPs/LCE actuator could generate incompatible strain to propel the actuator roll forward. Compared with other millimeter-scale NIR light-induced soft actuators reported in the literature, 6,[47][48][49][50] the CPs/LCE actuators proposed here exhibit a faster response time (within 1 s), more significant deformation potential (1801 bending angle) and higher locomotion speed (0.47 mm s À1 ).…”
Section: Introductionmentioning
confidence: 82%
“…A detailed description of the synthetic procedure is provided in the Supporting Information (Scheme S1, Supporting Information). The chemical structure of DPPTA is well characterized by 1 H-NMR and 13 C-NMR spectroscopy (for details see the Supporting Information). To study the photoisomerization, we characterized photophysical and photoluminescence behaviors of DPPTA under light irradiation, including 1 H-NMR spectra, UV-vis absorption spectra and fluorescence spectra of DPPTA in solution (see Figures S1-S3, Supporting Information).…”
Section: Characterization Of H-bonded Complex Dppta-ahbamentioning
confidence: 99%
“…[ 19–22 ] Combining light‐driven LCN films combined with piezoelectric materials, such as PVDF, can further convert mechanical motions to electrical energy. [ 23–26 ] Wei et al reported a near‐infrared (NIR) light‐triggered generator composed of a liquid crystal elastomer (LCE) and PVDF film. [ 26 ] Tang et al reported an optical pendulum generator that could generate electricity continuously by liquid crystalline actuators’ oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23–26 ] Wei et al reported a near‐infrared (NIR) light‐triggered generator composed of a liquid crystal elastomer (LCE) and PVDF film. [ 26 ] Tang et al reported an optical pendulum generator that could generate electricity continuously by liquid crystalline actuators’ oscillation. [ 27 ] However, the low‐grade waste heat harvester based on LCNs is seldom reported and most of such actuators with the separated stimuli active film from the generation film relied on repeatedly switching light stimulus on–off, [ 23,24,27 ] which strongly limits their practical applications and the integration of the device.…”
Section: Introductionmentioning
confidence: 99%